2021
DOI: 10.1002/micr.30738
|View full text |Cite
|
Sign up to set email alerts
|

Comparing digital replantation versus revision amputation patient reported outcomes for traumatic digital amputations of the hand: A systematic review and meta‐analysis

Abstract: Purpose Adults with traumatic digital amputation (TDA) of the hand may be managed with replantation or revision amputation. To date, there is no systematic review evaluating patient reported outcomes (PROs) comparing replantation versus revision amputation. Methods Three databases (MEDLINE, EMBASE, and PubMed) were systematically searched in duplicate from inception until June 13, 2019 using Covidence software. Studies comparing replantation versus revision amputation outcomes were considered for inclusion. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Limited power limited this study, as the replantation surgery is an infrequent occurrence and no prospective national database exists to track occurrence and outcomes. 24,25 A second limitation is with the restraints of the database itself. These include no outcome data other than failure/readmission, no zone of injury documented, mechanism of injury, hospital volume, surgeon volume, and time from injury to surgery, all of which have been demonstrated to be impactful in replantation success.…”
Section: Table 3 Comparisons Between Characteristics Of Patients Unde...mentioning
confidence: 99%
“…Limited power limited this study, as the replantation surgery is an infrequent occurrence and no prospective national database exists to track occurrence and outcomes. 24,25 A second limitation is with the restraints of the database itself. These include no outcome data other than failure/readmission, no zone of injury documented, mechanism of injury, hospital volume, surgeon volume, and time from injury to surgery, all of which have been demonstrated to be impactful in replantation success.…”
Section: Table 3 Comparisons Between Characteristics Of Patients Unde...mentioning
confidence: 99%
“…There is also a scarcity of PROM data after revision amputation, and the data that are available suggest that minor disability occurs [8,12,16,21,43,44,48,49]. Other studies reported fewer days of hospitalization, a lower number of secondary operations, and more rapid return to work compared with replantation surgery [5,12,21,43,48]. We therefore wished to evaluate the outcomes of replantation and revision amputation after traumatic distal upper extremity amputation.…”
Section: Introductionmentioning
confidence: 99%
“…In prior studies, functional results have been mostly reported after thumb replantation [ 12 14 ]. Larger multicenter studies or meta-analyses comparing digital replantation versus revision amputation were recently performed and were based on patient-reported outcomes assessed by questionnaires [ 15 17 ]. So far, only a few studies have compared functional outcome and recovery of sensibility between digit replantation and amputation [ 14 , 18 ].…”
Section: Introductionmentioning
confidence: 99%